The Anomaly of the Village Government in Establishing Village Owned Enterprise - Busyra Azheri; Upita Anggunsuri (Hasanuddin Law Review, 2018)
Village Owned Enterprise is an important part of the form of empowerment economic community at the village. Given, the urgency of the existence of Village Owned Enterprise, the government through the Regulation of Ministry of Villages, Disadvantaged Regions and Transmigration No. 5 of 2015 stated that one of the priorities of the use of village funds is for the establishment and development of Village Owned Enterprise. While the mechanism of establishment of Village Owned Enterprise is based on the result of village consultative meeting involving element of village government, element of village consultative body, and elements of community figures. The result of the village consultative meeting is implemented in form Village Regulation. However, it causes anomaly related to the status of Village Owned Enterprise, because it does not have to be legal entity in Regulation of Ministry of Villages meanwhile it has to be legal entity in Regulation of Minister of Home Affairs No. 39 of 2010 on Village Owned Enterprise.